2017
DOI: 10.24912/jm.v20i3.11
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Karakteristik Psikologis, Sikap Berwirausaha, Dan Norma Subyektif Terhadap Niat Berwirausaha

Abstract: Entrepreneurship education is currently done in college, with the intention to form youth entrepreneur and succesful independent life; many factors thought to influence the formation of entrepreneurship intention to young people who have got entrepreneurship education. The research aims to test the research model that describes the relationship between psychological characteristics constructs, subjective norm constructs, attitudes to entrepreneurship constructs, and entrepreneurship intention constructs among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 8 publications
1
4
1
4
Order By: Relevance
“…Several studies have revealed that psychological capital, including its four attributes, affects the increasing intention in entrepreneurship (Ajzen, 2011). However, Santoso and Oetomo (2016) found that psychological capital did not affect entrepreneurial intentions. Meanwhile, Chan et al (2017) stated that when an individual has psychological capital, it can help him/her to work effectively in pursuing aspirations by helping him/her face failure or disappointment during the entrepreneurship process.…”
Section: Suryani and Megawatimentioning
confidence: 97%
“…Several studies have revealed that psychological capital, including its four attributes, affects the increasing intention in entrepreneurship (Ajzen, 2011). However, Santoso and Oetomo (2016) found that psychological capital did not affect entrepreneurial intentions. Meanwhile, Chan et al (2017) stated that when an individual has psychological capital, it can help him/her to work effectively in pursuing aspirations by helping him/her face failure or disappointment during the entrepreneurship process.…”
Section: Suryani and Megawatimentioning
confidence: 97%
“…Oleh karena itu keberhasilan dalam menumbuhkan sikap berwirausaha mahasiswa yaitu tingkat pendidikan untuk itu perlu didorong terciptanya program pendidikan dan pelatihan formal untuk menumbuh kembangkan pengetahuan kewirausahaan. Temuan dalam penelitian ini juga mendukung penelitian (Tshikovhi dan Shambare, 2015;Pramudita, 2019;Santoso dan Oetomo, 2016) menunjukkan bahwa sikap mandiri secara langsung pengaruh signifikan terhadap minat berwirausaha mahasiswa.…”
Section: Sikap Mandiri Memediasi Pengaruh Pembelajaran Kewirausahaan ...unclassified
“…Prinsip model niat ditentukan oleh sikap, individu yang memandang sikap kewirausahaan menguntungkan akan meningkatkan niat untuk melaksanakan kegiatan kewirausahaan (Botsaris & Vamvaka, 2014:4). Penelitian yang telah dilakukan mengenai niat berwirausaha di kalangan mahasiswa Indonesia mengindikasikan permasalahan karakteristik individu yang hampir sama, dengan dipengaruhi faktor sikap kewirausahaan ketertarikan untuk berkarir pada bidang kewirausahaan atau bisnis menjadi meningkat (Sutanto, 2014;Santoso & Oetomo, 2016).…”
Section: Universitasunclassified